The recognition of Tibouchina setosociliata Cogn. (Melastomataceae, Melastomeae) and its transfer to Pleroma D. Don - Meyer, Fabrício Schmitz; Matos, Fernando Bittencourt De (Phytotaxa, 2017)
Pleroma setosociliatum (Cogn.) F.S. Mey. & F.B. Matos, from the states of Paraná and Santa Catarina, Brazil, has been indicated, still as a name in Tibouchina, as a synonym of T. dubia (Cham.) Cogn. on several floras and electronic databases. However, field observations and a more detailed analysis of herbarium specimens, including the types, led to the conclusion that these two species are distinct. They differ from each other not only in geographic distribuition, but also in growth habit, leaf size, indument, and dimensions of the connectives on antesepalous stamens. Tibouchina setosociliata is here transferred to Pleroma on the basis of morphology and results of a previously published molecular phylogeny.